Relationship Between Online Reservation Quality Through the Mangusada Mobile Application and Outpatient Satisfaction at Mangusada Regional Hospital, Badung Regency - Anak Agung Gde Putra Mahendra; Cokorda Bagus Jaya Lesmana; Pande Putu Januraga (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: The online reservation system implemented through the Mangusada Mobile application aims to enhance efficiency and improve patient satisfaction in outpatient care; however, system quality and user-related challenges may influence patient experience. This study examined system quality using the End User Computing Satisfaction (EUCS) model, levels of outpatient satisfaction, user constraints, and the relationship between system quality and outpatient satisfaction. Materials and Methods: A quantitative correlational survey was conducted among users of the Mangusada Mobile application. Results and Discussion: Findings showed that all EUCS dimensions scored above 80% and were categorized as “very satisfactory,” with the highest score in content (86.02%) and the lowest in timeliness (80.25%). Most patients reported high satisfaction with outpatient services, particularly in tangibles, reliability, responsiveness, empathy, and assurance. The most frequent constraints were internet connectivity issues (48.27%), user-related difficulties (30.94%), and technical problems (20.79%), which affected perceptions of timeliness. A significant association was found between online reservation quality and outpatient satisfaction (p < 0.001), with patients who perceived good system quality being 7.277 times more likely to be satisfied. Conclusion: These findings highlight that online reservation system quality is a critical determinant of outpatient satisfaction.